Relationship between serum immunological biomarkers and small airway obstruction in patients with mild-to-moderate asthma and allergic rhinitis and their prognostic value - Xue, Jing; Liu, Xin; Bai, Cairong; Zuo, Yali; Hao, Wendong (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the correlation between various serum immunological biomarkers and small airway obstruction (SAO) in affected children, and their prognostic value. Methods: All study participants were recruited from Yulin Hospital, the First Affiliated Hospital of Xi'an Jiaotong University in Yulin City, spanning the period from February 2023 to March 2024. A cohort of 295 children diagnosed with asthma, categorized into two groups: asthma group (n=178) and asthma with allergic rhinitis group (n=117). Peripheral venous blood was collected from both groups to measure serum levels of TIgE, CRP, EOS and IL-6 using ELISA, standardized laboratory assays. All participants underwent pulmonary function testing, including FEV1, FVC, FEV1/FVC ratio, and PEF measurements, performed in accordance with ATS/ERS guidelines. Statistical analyses compared biomarker levels and lung function parameters between the groups, with significance set at p Less-Than 0.05. Results: A significant negative correlation was found between serum IL-6 levels and the SAO parameters MMEF25-75%pred and FEF%50pred (r=-0.564, p Less-Than 0.05; r=-0.521, p Less-Than 0.05) in the asthma with allergic rhinitis group. The cut-off values for IgE, CRP and IL-6 were 337.80 IU/mL (AUC=0.816, 95%CI:0.749~0.894; sensitivity 64.31%, specificity 87.61%), 24.51mg/L (AUC=0.848, 95%CI:0.779~0.922; sensitivity 75.73%, specificity 81.44%) and 38.75pg/mL (AUC=0.748, 95%CI:0.661~0.826; sensitivity 62.95%, specificity 82.06%), respectively. In addition, the AUC, sensitivity, and specificity of the combined diagnosis of IgE, CRP, and IL-6 were 0.885,78.51%, and 89.26%, respectively. Conclusion: All three biomarkers of TIgE, CRP, and IL-6 were found to be associated with SAO, the combination of these three biomarkers demonstrated high diagnostic power for identifying pediatric patients with both asthma and allergic rhinitis. Keywords: Asthma, Allergic rhinitis, IL-6, Small airway obstruction.